The Principal’s Leadership Strategy in Developing the Religious Character of Students at SMK Muhammadiyah 1 Sragen - Irma Parina; Istanto Istanto (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study aims to examine the principal's leadership role in fostering religious character at SMK Muhammadiyah 1 Sragen. The background of the problem indicates that the school's religious character is not yet fully optimal, thus requiring the principal's active involvement in instilling religious values into daily routines. This study focuses on how the principal's leadership influences the implementation of religious character in the school environment, including the strategies employed and the obstacles encountered. This study uses a qualitative case study approach, including in-depth interviews with the principal. The findings indicate that the principal successfully builds religious character through exemplary behavior, daily worship habits, the provision of religious symbols, and regular school studies. However, the main challenge faced is the lack of discipline among some students in carrying out religious activities. This study concludes that effective school leadership, supported by continuous assessment and collaboration across the entire school community, can foster a conducive environment for the development of student character grounded in religious principles. Prospects for further research include steps to maintain and enhance the established religious culture.